Influence of the increase density and resin level on mechanical properties of Chusquea culeou particleboard agglomerated with ureaformaldehyde - Rijo, Carlos (Bosque (Valdivia), 1988)
The effect of increasing solid resin, and the density of manufactured Chusquea culeou Desv. particleboard, agglomerated with ureaformaldehyde was studied. The one-layer boards were 11 mm thick, and were manufactured using shaves like those used in coke layers. The Densities studied were 450, 550, 650 and 750 Kg/m3 and the resin levels 6, 7, 8, 9 and 10% based on oven-dry shave weigth. Mechanical properties were tested according to DIN standard, and were analized by linear regression. A high correlation between studied mechanical properties and density was found. The adhesive effect was significant for the bending strength only over a 600 Kg/m3 density and with a resin level over 8%. Concerning internal bond, the increase resin level is advantageous in all studied densities.